A MACROKINETIC STUDY OF THE OXIDATION OF METHANOL TO FORMALDEHYDE ON Fe2O3 – MoO3 OXIDE CATALYST - DRĂGAN, Simion; KULIC, Ivette (Studia Universitatis Babeș-Bolyai Chemia, 2016)
In this paper, a kinetic study about the oxidation of methanol to formaldehyde on Fe2O3-MoO3 oxide catalyst was investigated. Results about the changes of the conversion at different contact times and the way the composition of the mixture, respectively temperature influence the oxidation process, is submitted. The parameters were elected so that they match with those of the existing industrial reactors. We analyzed the influence of the above-mentioned parameters on the rate of the process. Processing the experimental results in coordinates allowed the determination of the activation energy and the establishment of the corresponding mechanisms. The results, Ea=57.23 kJ/mol, indicate that under 520K the mass transformation processes (chemical reaction, adsorption – desorption) are the limiting ones the oxidation process. At temperatures higher than 535K the value of the activation energy, Ea=9.39 kJ/mol, emphasizes that limiting are the inner/outer diffusion phenomena. In the temperature range 520K – 535K, when Ea=25 – 42 kJ/mol, the process is carried out after a combined macrokinetic model (mass transfer –transformation).